The literature component in Malaysian secondary English language syllabus: aiding or impeding language learning? a participatory action research project - Idrus, Faizah; Che Haron, Sabrina (Institut Terjemahan & Buku Malaysia, 2016)
This study is aimed at finding out how students and teachers at a selected school in Gombak district perceived the teaching and learning of the literature component of the English Language subject. It also focuses on the aspects of the practices in the literature classrooms as to whether they aid or impede English language learning in general. A mixed method design was applied to this investigation employing the concurrent triangulation strategy (Creswell, 2005), guided by the participatory Action Research Framework (McIntyre, 2007). The qualitative data which includes semi-structure interviews with 3 teachers and 5 students is the main data input, whilst a set of questionnaire distributed to 381 students supports the qualitative findings. The results of this study revealed that as much as being interested in the literature lessons, some students find that it has not improved their proficiency as well as the other skills such as writing, listening, and speaking. Similarly, teachers are more skeptical of students’ improvement in all skills (RWLS) but agree that some students seem to enjoy the literature component more than the other components in the English language subject. These results corroborate with the findings of a few other studies in this area which point to the direction of the need to reexamine the effectiveness of factors such as materials used, teaching and learning strategies and also teacher-preparation programs to ensure that the literature component is not a mere unit in the English language syllabus for the students to pass the exam and the teachers to get by